Deletion of the EphA2 receptor exacerbates myocardial injury and the progression of ischemic cardiomyopathy - O'Neal, Wesley T.; Griffin, William F.; Kent, Susan D.; Faiz, Filza; Hodges, Jonathan; Vuncannon, Jackson; Virag, Jitka A. I. (Frontiers in Physiology, 2014)
EphrinA1-EphA-receptor signaling is protective during myocardial infarction (MI). The EphA2-receptor (EphA2-R) potentially mediates cardiomyocyte survival. To determine the role of the EphA2-R in acute non-reperfused myocardial injury in vivo, infarct size, inflammatory cell density, NF-κB, p-AKT/Akt, and MMP-2 protein levels, and changes in ephrinA1/EphA2-R gene expression profile were assessed 4 days post-MI in B6129 wild-type (WT) and EphA2-R-mutant (EphA2-R-M) mice lacking a functional EphA2-R. Fibrosis, capillary density, morphometry of left ventricular chamber and infarct dimensions, and cardiac function also were measured 4 weeks post-MI to determine the extent of ventricular remodeling. EphA2-R-M infarct size and area of residual necrosis were 31.7% and 113% greater than WT hearts, respectively. Neutrophil and macrophage infiltration were increased by 46% and 84% in EphA2-R-M hearts compared with WT, respectively. NF-κB protein expression was 1.9-fold greater in EphA2-R-M hearts at baseline and 56% less NF-κB after infarction compared with WT. EphA6 gene expression was 2.5-fold higher at baseline and increased 9.8-fold 4 days post-MI in EphA2-R-M hearts compared with WT. EphrinA1 gene expression in EphA2-R-M hearts was unchanged at baseline and decreased by 42% 4 days post- MI compared with WT hearts. EphA2-R-M hearts had 66.7% less expression of total Akt protein and 59% less p-Akt protein than WT hearts post-MI. EphA2-R-M hearts 4 weeks post-MI had increased chamber dilation and interstitial fibrosis and decreased MMP-2 expression and capillary density compared with WT. In conclusion, the EphA2-R is necessary to appropriately modulate the inflammatory response and severity of early injury during acute MI, thereby influencing the progression of ischemic cardiomyopathy.